EFFECT OF PVD COATED TOOLS ON EUTECTIC ALUMINIUM ALLOY DURING DRY MACHINING PROCESS - Tanmay Thombare1, B.R. Ingale2 Digmber Kashid3 (International Journal of Innovations in Engineering Research and Technology, 2022)
Aluminium Alloy is widely used in various Industries like Aerospace, Automobile etc. due to their peculiar character weight by volume ratio. Addition Silicon not only increases the strength of the alloy but also helps to perform smooth machining. Silicon in the Al alloy is about 12% is commonly known as Eutectic Al Alloy. Machining is a further challenge for this Eutectic alloy. Dry machining process is an economic and environmental healthy process. In the present study Eutectic Aluminium alloy is machined using PVD coated HC,AlTiN and Uncoated Carbide cutting tool. Minitab statistical software is used to produce L27 Array for 3 factor and 3 levels of variables to conduct turning experiment. Average Surface roughnesses are recorded to optimize the cutting parameters for each tool using Taguchi analysis for the dry machining process. Hard Carbon coated tool machining gives minimum Ra= 0.615 µm at 2000 rpm Speed, 0.02 mm/rev feed rate and 0.25mm depth of cut. The study also shows that coated tools shows appreciable results compared with uncoated tools to achieve optimized surface finish.